(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
In this paper we study if hedge funds have added value in a consistent way, for the Spanish retail investor, during the past six years. We find that hedge funds add value five of the six years on this study. They are specially interesting for those investors with low to medium risk profile. Including hedge funds in a portfolio can be very rewarding in the long run as can be seen when we consider the results of the six years as a whole. The results of this study are consistent with the vast majority of the literature in this area.